Simulation of microscopic fracture characteristics of fractured rock based on CZM-FDEM method - Zou, Qianjin; Li, Haigang; Zheng, Yu; Zhang, Xinru; Wang, Liuyue; Zhang, Jiyong (Scientific reports, 2025)
Microstructural damage is an important cause of macrofracture in fissured rocks. To investigate the microscopic fracture mechanism of fissured rocks, a fissured rock model was established using the CZM-FDEM method. The model considers the mechanical behaviour of cohesive elements between particles within the rock and the propagation of cracks through the damage of cohesive elements. In the damage evolution stage of the cohesive element ontological relationship, the damage variable D is introduced to describe the damage degree of the unit stiffness, which in turn characterises the microscopic damage features of the model. The results show that the stress–strain curve morphology and strength characteristics of the numerical model are in high agreement with the indoor test results, and the model exhibits significant advantages in crack extension, which verifies the applicability of the method in rock fracture simulation. The microscopic damage field exhibits X-shaped conjugate fracture characteristics, and the crack inclination leads to differences in fracture paths by changing the stress field distribution at the crack tip. The number of cohesive element fractures on the microscopic scale shows a high correlation with the macroscopic strength, and the cleavage inclination angle directly affects the load carrying capacity of the structure by regulating the fracture element rate.